Business characteristics and efficiency of rural tourism enterprises: an empirical study from China. Issue 6 (3rd June 2018) - Li, Tao; Liu, Jiaming; Zhu, He; Zhang, Shuying
ABSTRACT: The booming rural tourism (RT) has broadened ways for rural revitalization and poverty alleviation strategy in China. Rural tourism enterprises (RTEs), as the core operator and a hinge delivering its benefits to rural communities, play a critical role in the achievement of RT expectation on rural revitalization. To address the research gap in business characteristics and efficiency of RTEs, and make the theoretical contribution to rural business and tourism management, this study collected and analyzed the business data with investors or managers of 60 national-class RTEs in Jiangsu Province, north Yangtze River Delta of China. The results showed that business characteristics of RTEs varied with their property, business strategy, and rural industrial base. Flexible and sustainable business operation and comprehensive regional development have a profound influence on business efficiency that presented multi spatial disparity from inter-regional and intra-regional views, respectively. In addition, the political and practical implications on rural business and RTEs for research and practice were also discussed.